Corrigendum to ‘A U.S. scientific community review of carbon cycle science gaps and opportunities to better support earth system science and carbon management’ [Earth-Science Reviews 278 (2026) 1-28] - N.C. Parazoo; D. Carroll; J.B. Abshire; Y.M. Bar-On; R.A. Birdsey; A.A. Bloom; K.W. Bowman; R.K. Braghiere; L.M. Bruhwiler; B. Byrne; A. Chatterjee; D. Crisp; et al. (Earth-Science Reviews, 2026)

A U.S. scientific community review of carbon cycle science gaps and opportunities to better support earth system science and carbon management - N.C. Parazoo; D. Carroll; J.B. Abshire; Y.M. Bar-On; R.A. Birdsey; A.A. Bloom; K.W. Bowman; R.K. Braghiere; L.M. Bruhwiler; B. Byrne; A. Chatterjee; D. Crisp; et al. (Earth-Science Reviews, 2026)

Spatiotemporal evolution of the quartzofeldspathic gneisses of the Vinjamuru domain, Eastern Ghats Belt, India: Implications for the late Paleoproterozoic crustal growth in a craton-margin orogenic belt - Amitava Chatterjee; Suresh C. Patel; Chang Whan Oh; Janisar M. Sheikh (Lithos, 2026)

Decoding the genetic basis of Cnaphalocrocis medinalis (Guenee) resistance in rice landraces using SSR markers and association mapping - Soumya Shephalika Dash; Prasanthi Golive; Prakash Chandra Rath; Hirak Chatterjee; Arup Kumar Mukherjee; Anjan Kumar Nayak; Partha Sarathi Tripathy; Sucharita Mohapatra; Anilkumar C; Shyamaranjan Das Mohapatra (Protoplasma, 2026)

Local and Landscape‐Level Environmental Conditions Drive Habitat Selection Across Terrestrial Mammal Species - Björn H. Franke; Aafke M. Schipper; Tal Avgar; Luca Börger; Nilanjan Chatterjee; Thomas Müller; Brian J. Smith; Briana Abrahms; Abdullahi H. Ali; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; et al. (Global Ecology and Biogeography, 2026)
Aim Animal movements are a fundamental process affecting communities and ecosystems. Quantifying habitat selection across species and habitats is key for understanding how animals respond to environmental change. Currently, we lack comparative studies that examine how habitat selection varies across species traits and landscapes. We aim to quantify global patterns of habitat selection to help understand the fundamental drivers of movement behaviour. Location Global. Time Period Contemporary. Major Taxa Studied Terrestrial mammals. Methods We estimated selection coefficients for terrain ruggedness, vegetation productivity, human population density and distance to roads of individual terrestrial mammals through step‐selection analysis of 1344 GPS tracks across 48 species. We quantified intra‐ and interspecific variation and tested whether selection coefficients were associated with species traits and habitat availability. Results We observe an overall avoidance of roads and areas of high human population density as well as rugged terrain, with a large proportion of individuals selecting for areas of intermediate NDVI. However, we also found large intraspecific variation in habitat selection and show that this variation is predicted by local and landscape‐level environmental conditions rather than species traits. Individuals in more remote areas exhibited weaker functional responses to human presence than those in more disturbed areas. Avoidance of rugged terrain is also context‐dependent, with stronger avoidance when local ruggedness is high. The only exception to the observed intraspecific variability is consistent species‐level responses to road proximity. Main Conclusions Our findings contribute to the understanding of habitat selection by terrestrial mammals, showing that selection is largely shaped by environmental conditions and that animals exhibit high plasticity in their responses. Our results also provide further evidence for the significant impact of roads on animal movement. These insights can help us to understand the potential effects of environmental change on the behaviour of mammal species around the world.

Beyond the target: the ecotoxicological impact of flubendiamide in natural ecosystems - T. Roy; S. Ghosh; A. H. Mandal; N. C. Saha; S. Chatterjee; D. S. Paria; C. R. Multisanti; C. Faggio; S. Saha (International Journal of Environmental Science and Technology, 2026)

Rapid 21st Century Warming in the Southern Subtropical Indian Ocean Driven by Altered Inter‐Basin Connections - C. K. Sajidh; Abhisek Chatterjee; Raghu Murtugudde; Michael J. McPhaden; S. S. C. Shenoi; P. N. Vinayachandran (International Journal of Climatology, 2026)
The Indian Ocean has been warming rapidly over the last few decades. However, this warming has not been uniform, with the southern subtropical Indian Ocean (STIO, 15°S–35°S) cooling until the late 20th century and then warming abruptly. We show that the Indonesian Throughflow (ITF) into the Indian Ocean exhibits strong decadal variability with a weaker negative trend over the recent decades, and hence cannot explain the continued heat gain by the upper ocean of the STIO at a rate of 0.41 (± 0.02) × 10 22 J/decade. An increased ITF during the hiatus in global surface warming initiated the STIO warming, resulting in a weaker Mascarene high and its decoupling from the Southern Ocean atmospheric variability. This enhanced Tasman inflow into the Indian Ocean and weakened Agulhas outflow offsetting the recently weakened ITF, caused a positive feedback that continued to warm the upper ocean of the STIO.

Neoarchean crustal evolution in the Madras Block: Geochemical and petrological evidence from felsic gneiss and amphibolite - P.V. Thanooja; K. Sajeev; M. Satish-Kumar; I.S. Williams; T. Takahashi; C. Chatterjee (Polar Science, 2025)

A worldwide aerosol phenomenology: Elemental and organic carbon in PM2.5 and PM10 - Jean-Philippe Putaud; Fabrizia Cavalli; Karl Espen Yttri; Judith C. Chow; John G. Watson; Baerbel Sinha; Chandra Venkataraman; Fumikazu Ikemori; Jean-Luc Jaffrezo; Gaelle Uzu; Isabel Moreno; Radovan Krejci; et al. (Atmospheric Environment, 2025)

Formulation and evaluation of polymeric nanoparticles to improve in vivo chemotherapeutic efficacy of mangiferin against breast cancer - Pratik Chakraborty; Ananya Das; Sharmistha Chatterjee; Aparajita Bairagi; Hiranmoy Bhattacharya; Chiranjib Bhattacharyya; Nabanita Chatterjee; Parames C. Sil; Saikat Dewanjee (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Insights from untargeted metabolomics and molecular networking on the effect of infrared drying and electrical oven drying of Turbinaria conoides (J. Agardh) Kuzing for nutraceutical application - Dona Jaiju; Rajesh Ravichandran; Pranamya C. Haridas; Aniesrani Delfia; Devananda Uchoi; Niladri Sekhar Chatterjee (Food and Humanity, 2025)

Identifying differential survival, photolocomotor behavior, and gene expression responses to cylindrospermopsin in Danio rerio and Pimephales promelas - Kendall R. Scarlett; Laura M. Langan; Lea M. Lovin; Abigail N. Henke; Sujin Kim; Kevin M. Stroski; C. Kevin Chambliss; Saurabh Chatterjee; J. Thad Scott; Bryan W. Brooks (Science of The Total Environment, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

LP-12 Behavioral alterations by micro(nano) plastics: insights from Zebrafish and Caenorhabditis elegans - C. Kempkens Palacios; J. Le Du-Carrée; R. Almeda; S.H. Keiter; E. Alfaro-Moreno; N. Chatterjee (Toxicology Letters, 2024)

Data processing of visible emission line coronagraph onboard ADITYA-L1 - Muthu Priyal; Jagdev Singh; B. Raghavendra Prasad; Chavali Sumana; Varun Kumar; Shalabh Mishra; S.N. Venkata; G. Sindhuja; K. Sasikumar Raja; Amit Kumar; Sanal krishnan; Bhavana S. Hegde; et al. (Advances in Space Research, 2024)

Authentication of the species identity of squid rings using UHPLC-Q-Orbitrap MS/MS-based lipidome fingerprinting and chemoinformatics - Pranamya C. Haridas; Rajesh Ravichandran; Nasiruddin Shaikh; Pankaj Kishore; Satyen Kumar Panda; Kaushik Banerjee; Niladri Sekhar Chatterjee (Food Chemistry, 2024)

Modeling real-world diesel car tailpipe emissions using regression-based approaches - C Chandrashekar; Pritha Chatterjee; Digvijay S. Pawar (Transportation Research Part D: Transport and Environment, 2024)

Exploring the uncertainty of machine learning models and geostatistical mapping of rare earth element potential in Indiana coals, USA - Snehamoy Chatterjee; C. Özgen Karacan; Maria Mastalerz (International Journal of Coal Geology, 2024)

Review of Solar Energetic Particle Prediction Models - Kathryn Whitman; Ricky Egeland; Ian G. Richardson; Clayton Allison; Philip Quinn; Janet Barzilla; Irina Kitiashvili; Viacheslav Sadykov; Hazel M. Bain; Mark Dierckxsens; M. Leila Mays; Tilaye Tadesse; et al. (Advances in Space Research, 2023)

Global taxonomic, functional, and phylogenetic diversity of bees in apple orchards - N. Leclercq; L. Marshall; T. Weekers; P. Basu; D. Benda; D. Bevk; R. Bhattacharya; P. Bogusch; A. Bontšutšnaja; L. Bortolotti; N. Cabirol; E. Calderón-Uraga; et al. (Science of The Total Environment, 2023)

Reassessing the availability of crop residue as a bioenergy resource in India: A field-survey based study - Taveen S. Kapoor; Chimurkar Navinya; Gupta Anurag; Pradnya Lokhande; Shubham Rathi; Anubha Goel; Renuka Sharma; Rahul Arya; Tuhin K. Mandal; K.P. Jithin; Shiva Nagendra; Mohd Imran; et al. (Journal of Environmental Management, 2023)

The transposable element-derived transcript of LIN28B has a placental origin and is not specific to tumours - Chiemi F. Lynch-Sutherland; Lorissa I. McDougall; Peter A. Stockwell; Suzan N. Almomani; Robert J. Weeks; Jackie L. Ludgate; Teena K. J. B. Gamage; Aniruddha Chatterjee; Joanna L. James; Michael R. Eccles; Erin C. Macaulay (Molecular Genetics and Genomics, 2023)
Transposable elements (TEs) are genetic elements that have evolved as crucial regulators of human development and cancer, functioning as both genes and regulatory elements. When TEs become dysregulated in cancer cells, they can serve as alternate promoters to activate oncogenes, a process known as onco-exaptation. This study aimed to explore the expression and epigenetic regulation of onco-exaptation events in early human developmental tissues. We discovered co-expression of some TEs and oncogenes in human embryonic stem cells and first trimester and term placental tissues. Previous studies identified onco-exaptation events in various cancer types, including an AluJb SINE element– LIN28B interaction in lung cancer cells, and showed that the TE-derived LIN28B transcript is associated with poor patient prognosis in hepatocellular carcinoma. This study further characterized the AluJb– LIN28B transcript and confirmed that its expression is restricted to the placenta. Targeted DNA methylation analysis revealed differential methylation of the two LIN28B promoters between placenta and healthy somatic tissues, indicating that some TE–oncogene interactions are not cancer-specific but arise from the epigenetic reactivation of developmental TE-derived regulatory events. In conclusion, our findings provide evidence that some TE–oncogene interactions are not limited to cancer and may originate from the epigenetic reactivation of TE-derived regulatory events that are involved in early development. These insights broaden our understanding of the role of TEs in gene regulation and suggest the potential importance of targeting TEs in cancer therapy beyond their conventional use as cancer-specific markers.

Indian Ocean dynamic sea level, its variability and projections in CMIP6 models - C. K. Sajidh; Abhisek Chatterjee (Climate Dynamics, 2023)

Halogen enrichment in the North American lithospheric mantle from the dehydration of the Farallon plate - George Segee-Wright; Jaime D. Barnes; John C. Lassiter; Duncan J. Holmes; Grace M. Beaudoin; Rudra Chatterjee; Daniel F. Stockli; J. Elis Hoffmann; Timm John (Geochimica et Cosmochimica Acta, 2023)

Effect of exogenous fibrolytic enzymes supplementation on voluntary intake, availability of nutrients and growth performance in Black Bengal kids (Capra hircus) - Manoj Kumar; A. Chatterjee; T.K. Dutta; Yora Reena; Asif Mohammad; C. Bhakat; Saroj Rai; D.K. Mandal; M. Karunakaran (Small Ruminant Research, 2023)

Modelling Release Kinetics and Path Analysis of Phosphorus in Acid Soil as Influenced by Phosphorus Solubilizers - Dibyendu Chatterjee; Konsam Vikramjeet; Totan Adak; Z. James Kikon; Sayon Mukherjee; Rukuosietuo Kuotsu; Bidyut C Deka; Saikat Ranjan Das (Journal of Soil Science and Plant Nutrition, 2022)

Phlorotannins–bioactivity and extraction perspectives - Lekshmi R. G. Kumar; Preethy Treesa Paul; K. K. Anas; C. S. Tejpal; N. S. Chatterjee; T. K. Anupama; Suseela Mathew; C. N. Ravishankar (Journal of Applied Phycology, 2022)

Advances in analytical solutions for time-dependent solute transport model - Rohit Kumar; Ayan Chatterjee; Mritunjay Kumar Singh; Frank T-C Tsai (Journal of Earth System Science, 2022)

Effect of supplementation of phytogenic feed additives on intake, in vitro fermentation, growth performance and carcass traits in weaned Barbari kids reared under intensive feeding - Indu Chaturvedi; T. K. Dutta; P. K. Singh; A. Chatterjee; Dilip Kumar Mandal; C. Bhakat; Asif Mohammad; Arun K. Das (Tropical Animal Health and Production, 2022)

Modelling the Spatial Variation of Methane and Nitrous Oxide Emission from Rice Fields Using DNDC Model - Rahul Tripathi; M. Majhi; S. G. Sahu; S. Mohanty; K. C. Moharana; Md Shahid; C. K. Swain; B. Lal; P. Gautam; P. K. Dash; D. Chatterjee; A. Kumar; et al. (Journal of the Indian Society of Remote Sensing, 2021)

Progress in understanding of Indian Ocean circulation, variability, air–sea exchange, and impacts on biogeochemistry - Helen E. Phillips; Amit Tandon; Ryo Furue; Raleigh Hood; Caroline C. Ummenhofer; Jessica A. Benthuysen; Viviane Menezes; Shijian Hu; Ben Webber; Alejandra Sanchez-Franks; Deepak Cherian; Emily Shroyer; et al. (Ocean Science, 2021)
Over the past decade, our understanding of the Indian Ocean has advanced through concerted efforts toward measuring the ocean circulation and air–sea exchanges, detecting changes in water masses, and linking physical processes to ecologically important variables. New circulation pathways and mechanisms have been discovered that control atmospheric and oceanic mean state and variability. This review brings together new understanding of the ocean–atmosphere system in the Indian Ocean since the last comprehensive review, describing the Indian Ocean circulation patterns, air–sea interactions, and climate variability. Coordinated international focus on the Indian Ocean has motivated the application of new technologies to deliver higher-resolution observations and models of Indian Ocean processes. As a result we are discovering the importance of small-scale processes in setting the large-scale gradients and circulation, interactions between physical and biogeochemical processes, interactions between boundary currents and the interior, and interactions between the surface and the deep ocean. A newly discovered regional climate mode in the southeast Indian Ocean, the Ningaloo Niño, has instigated more regional air–sea coupling and marine heatwave research in the global oceans. In the last decade, we have seen rapid warming of the Indian Ocean overlaid with extremes in the form of marine heatwaves. These events have motivated studies that have delivered new insight into the variability in ocean heat content and exchanges in the Indian Ocean and have highlighted the critical role of the Indian Ocean as a clearing house for anthropogenic heat. This synthesis paper reviews the advances in these areas in the last decade.

Actual evapotranspiration and crop coefficients for tropical lowland rice (Oryza sativa L.) in eastern India - Sumanta Chatterjee; Paul C. Stoy; Manish Debnath; Amaresh Kumar Nayak; Chinmaya Kumar Swain; Rahul Tripathi; Dibyendu Chatterjee; Smruthi Sagarika Mahapatra; Ammara Talib; Himanshu Pathak (Theoretical and Applied Climatology, 2021)

Effect of Long-Term Organic Fertilization in Flooded Rice Soil on Phosphorus Transformation and Phosphate Solubilizing Microorganisms - Dibyendu Chatterjee; A. K. Nayak; Annapurna Mishra; C. K. Swain; U. Kumar; D. Bhaduri; P. Panneerselvam; B. Lal; P. Gautam; H. Pathak (Journal of Soil Science and Plant Nutrition, 2021)

Structural characterization and functional annotation of microbial proteases mined from solid tannery waste metagenome - Sumit K. Verma; Simerpreet Kaur; Arnav Tevetia; Sayan Chatterjee; Prakash C. Sharma (Biologia, 2021)

Inheritance of growth traits and impact of selection on carcass and egg quality traits in Vanashree, an improved indigenous chicken - Santosh Haunshi; Rajkumar U.; C. Paswan; L. L. L. Prince; R. N. Chatterjee (Tropical Animal Health and Production, 2021)

Genetic analysis of growth and egg production traits in synthetic colored broiler female line using animal model - L. Leslie Leo Prince; K. S. Rajaravindra; U. Rajkumar; B. L. N. Reddy; C. Paswan; S. Haunshi; R. N. Chatterjee (Tropical Animal Health and Production, 2020)

Assessing Impacts of Conservation Measures on Watershed Hydrology Using MIKE SHE Model in the Face of Climate Change - Gajanan Ramteke; R. Singh; C. Chatterjee (Water Resources Management, 2020)

Rain water resource management in mango orchards through micro-catchments - A. Mishra; A. Waghaye; C. Chatterjee; S. K. Rautaray (Sustainable Water Resources Management, 2020)

A model-based exploration of farm-household livelihood and nutrition indicators to guide nutrition-sensitive agriculture interventions - Natalia Estrada-Carmona; Jessica E. Raneri; Stephanie Alvarez; Carl Timler; Shantonu Abe Chatterjee; Lenora Ditzler; Gina Kennedy; Roseline Remans; Inge Brouwer; Karin Borgonjen-van den Berg; Elise F. Talsma; Jeroen C. J. Groot (Food Security, 2020)
Assessing progress towards healthier people, farms and landscapes through nutrition-sensitive agriculture (NSA) requires transdisciplinary methods with robust models and metrics. Farm-household models could facilitate disentangling the complex agriculture-nutrition nexus, by jointly assessing performance indicators on different farm system components such as farm productivity, farm environmental performance, household nutrition, and livelihoods. We, therefore, applied a farm-household model, FarmDESIGN, expanded to more comprehensively capture household nutrition and production diversity, diet diversity, and nutrient adequacy metrics. We estimated the potential contribution of an NSA intervention targeting the diversification of home gardens, aimed at reducing nutritional gaps and improving livelihoods in rural Vietnam. We addressed three central questions: (1) Do ‘Selected Crops’ (i.e. crops identified in a participatory process) in the intervention contribute to satisfying household dietary requirements?; (2) Does the adoption of Selected Crops contribute to improving household livelihoods (i.e. does it increase leisure time for non-earning activities as well as the dispensable budget)?; and (3) Do the proposed nutrition-related metrics estimate the contribution of home-garden diversification towards satisfying household dietary requirements? Results indicate trade-offs between nutrition and dispensable budget, with limited farm-household configurations leading to jointly improved nutrition and livelihoods. FarmDESIGN facilitated testing the robustness and limitations of commonly used metrics to monitor progress towards NSA. Results indicate that most of the production diversity metrics performed poorly at predicting desirable nutritional outcomes in this modelling study. This study demonstrates that farm-household models can facilitate anticipating the effect (positive or negative) of agricultural interventions on nutrition and the environment, identifying complementary interventions for significant and positive results and helping to foresee the trade-offs that farm-households could face. Furthermore, FarmDESIGN could contribute to identifying agreed-upon and robust metrics for measuring nutritional outcomes at the farm-household level, to allow comparability between contexts and NSA interventions.

Inter-relationship between intercepted radiation and rice yield influenced by transplanting time, method, and variety - Priyanka Gautam; B. Lal; A. K. Nayak; R. Raja; B. B. Panda; R. Tripathi; M. Shahid; U. Kumar; M. J. Baig; D. Chatterjee; C. K. Swain (International Journal of Biometeorology, 2019)

Wyrtki Jets: Role of intraseasonal forcing - S Prerna; Abhisek Chatterjee; A Mukherjee; M Ravichandran; S S C Shenoi (Journal of Earth System Science, 2019)

Leveraging model-informed approaches for drug discovery and development in the cardiovascular space - Marissa F. Dockendorf; Ryan C. Vargo; Ferdous Gheyas; Anne S. Y. Chain; Manash S. Chatterjee; Larissa A. Wenning (Journal of Pharmacokinetics and Pharmacodynamics, 2018)

Time dependent pharmacokinetics of pembrolizumab in patients with solid tumor and its correlation with best overall response - Hongshan Li; Jingyu Yu; Chao Liu; Jiang Liu; Sriram Subramaniam; Hong Zhao; Gideon M. Blumenthal; David C. Turner; Claire Li; Malidi Ahamadi; Rik de Greef; Manash Chatterjee; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2017)

Evidence for the existence of Persian Gulf Water and Red Sea Water in the Bay of Bengal - Vineet Jain; D. Shankar; P. N. Vinayachandran; A. Kankonkar; Abhisek Chatterjee; P. Amol; A. M. Almeida; G. S. Michael; A. Mukherjee; Meenakshi Chatterjee; R. Fernandes; R. Luis; et al. (Climate Dynamics, 2017)

Alr2954 of Anabaena sp. PCC 7120 with ADP-ribose pyrophosphatase activity bestows abiotic stress tolerance in Escherichia coli - Prashant Kumar Singh; Alok Kumar Shrivastava; Shilpi Singh; Ruchi Rai; Antra Chatterjee; L. C. Rai (Functional & Integrative Genomics, 2017)

Characterization of Vermicomposts Prepared from Agricultural Solid Wastes in North Eastern Hill Region of Nagaland, India - Dibyendu Chatterjee; Rukuosietuo Kuotsu; Z. James Kikon; Dibyendu Sarkar; Merasenla Ao; Sanjay Kumar Ray; Tanumoy Bera; Bidyut C. Deka (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

Mephebrindole, a synthetic indole analog coordinates the crosstalk between p38MAPK and eIF2α/ATF4/CHOP signalling pathways for induction of apoptosis in human breast carcinoma cells - Supriya Chakraborty; Swatilekha Ghosh; Bhaswati Banerjee; Abhishek Santra; Jyotsna Bhat; Arghya Adhikary; Subhrangsu Chatterjee; Anup K. Misra; Parimal C. Sen (Apoptosis, 2016)

Assessing current genetic status of the Hainan gibbon using historical and demographic baselines: implications for conservation management of species of extreme rarity - J. V. Bryant; D. Gottelli; X. Zeng; X. Hong; B. P. L. Chan; J. R. Fellowes; Y. Zhang; J. Luo; C. Durrant; T. Geissmann; H. J. Chatterjee; S. T. Turvey (Molecular Ecology, 2016)
Evidence‐based conservation planning is crucial for informing management decisions for species of extreme rarity, but collection of robust data on genetic status or other parameters can be extremely challenging for such species. The Hainan gibbon, possibly the world's rarest mammal, consists of a single population of ~25 individuals restricted to one protected area on Hainan Island, China, and has persisted for over 30 years at exceptionally low population size. Analysis of genotypes at 11 microsatellite loci from faecal samples for 36% of the current global population and tissue samples from 62% of existing historical museum specimens demonstrates limited current genetic diversity ( Na = 2.27, Ar = 2.24, H e = 0.43); diversity has declined since the 19th century and even further within the last 30 years, representing declines of ~30% from historical levels ( Na = 3.36, Ar = 3.29, H e = 0.63). Significant differentiation is seen between current and historical samples ( F ST = 0.156, P = 0.0315), and the current population exhibits extremely small N e (current N e = 2.16). There is evidence for both a recent population bottleneck and an earlier bottleneck, with population size already reasonably low by the late 19th century (historical N e = 1162.96). Individuals in the current population are related at the level of half‐ to full‐siblings between social groups, and full‐siblings or parent–offspring within a social group, suggesting that inbreeding is likely to increase in the future. The species' current reduced genetic diversity must be considered during conservation planning, particularly for expectations of likely population recovery, indicating that intensive, carefully planned management is essential.

Citric Acid Induced Potassium and Silicon Release in Alfisols, Vertisols and Inceptisols of India - Dibyendu Chatterjee; S. C. Datta; K. M. Manjaiah (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

Drosophila curviceps Species-Group (Diptera: Drosophilidae) from India, with Description of a New Species and Redescription of a Known Species - Sushmika Pradhan; Pradeep C. Sati; Rajendra S. Fartyal; Rabindra N. Chatterjee; Manisha Sarswat; Mukul C. Kandpal; Birendra K. Singh (Proceedings of the Zoological Society, 2015)

Obesity shifts house dust mite-induced airway cellular infiltration from eosinophils to macrophages: effects of glucocorticoid treatment - J. Diaz; L. Warren; L. Helfner; X. Xue; P. K. Chatterjee; M. Gupta; M. H. Solanki; M. Esposito; V. Bonagura; C. N. Metz (Immunologic Research, 2015)

A carbazole alkaloid deactivates mTOR through the suppression of rictor and that induces apoptosis in lung cancer cells - Priyajit Chatterjee; Soma Seal; Sandip Mukherjee; Rakesh Kundu; Mantu Bhuyan; Nabin C. Barua; Pranab K. Baruah; Santi Prasad Sinha Babu; Samir Bhattacharya (Molecular and Cellular Biochemistry, 2015)

Proceedings of the second international molecular pathological epidemiology (MPE) meeting - Shuji Ogino; Peter T. Campbell; Reiko Nishihara; Amanda I. Phipps; Andrew H. Beck; Mark E. Sherman; Andrew T. Chan; Melissa A. Troester; Adam J. Bass; Kathryn C. Fitzgerald; Rafael A. Irizarry; Karl T. Kelsey; et al. (Cancer Causes & Control, 2015)

Regional Flood Frequency Analysis using Soft Computing Techniques - Rakesh Kumar; Narendra K. Goel; Chandranath Chatterjee; Purna C. Nayak (Water Resources Management, 2015)

Role and Present Status of Biotechnology in Augmenting Poultry Productivity in India - C. Paswan; T. K. Bhattacharya; C. S. Nagaraj; R. N. Chatterjee; P. Guru Vishnu (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

New Mediterranean Marine biodiversity records (June 2013) - I. SIOKOU; A.S. ATES; D. AYAS; J. BEN SOUISSI; T. CHATTERJEE; M. DIMIZA; H. DURGHAM; K. DOGRAMMATZI; D. ERGUDEN; V. GERAKARIS; M. GREGO; Y. ISSARIS; et al. (Mediterranean Marine Science, 2013)
This paper concerns records of species that have extended their distribution in the Mediterranean Sea. The finding of the rare brackish angiosperm Althenia filiformis in the island of Cyprus is interesting since its insertion in the Red Data Book of the Flora of Cyprus is suggested. The following species enriched the flora or fauna lists of the relevant countries: the red alga Sebdenia dichotoma (Greece), the hydrachnid mite Pontarachna adriatica (Slovenia), and the thalassinid Gebiacantha talismani (Turkey). Several alien species were recorded in new Mediterranean localities. The record of the burrowing goby Trypauchen vagina in the North Levantine Sea (Turkish coast), suggests the start of spreading of this Lessepsian immigrant in the Mediterranean Sea. The findings of the following species indicate the extension of their occurrence in the Mediterranean Sea: the foraminifer Amphistegina lobifera (island of Zakynthos, Greece), the medusa Cassiopea andromeda (Syria), the copepod Centropages furcatus (Aegean Sea), the decapod shrimp Melicertus hathor (island of Kastellorizo, Greece), the crab Menoethius monoceros (Gulf of Tunis), the barnacles Balanus trigonus, Megabalanus tintinnabulum, Megabalanus coccopoma and the bivalves Chama asperella, Cucurbitula cymbium (Saronikos Gulf, Greece).

A new atlas of temperature and salinity for the North Indian Ocean - A CHATTERJEE; D SHANKAR; S S C SHENOI; G V REDDY; G S MICHAEL; M RAVICHANDRAN; V V GOPALKRISHNA; E P RAMA RAO; T V S UDAYA BHASKAR; V N SANJEEVAN (Journal of Earth System Science, 2012)

Chemical characterisation of meltwater draining from Gangotri Glacier, Garhwal Himalaya, India - VIRENDRA BAHADUR SINGH; AL RAMANATHAN; JOSE GEORGE POTTAKKAL; PARMANAND SHARMA; ANURAG LINDA; MOHD FAROOQ AZAM; C CHATTERJEE (Journal of Earth System Science, 2012)

Fine mode aerosol chemistry over a tropical urban atmosphere: characterization of ionic and carbonaceous species - A. Chatterjee; C. Dutta; T. K. Jana; S. Sen (Journal of Atmospheric Chemistry, 2012)

Acute and chronic effects of endosulfan on the haemato-immunological and histopathological responses of a threatened freshwater fish, spotted murrel, Channa punctatus - Kamal Sarma; A. K. Pal; N. P. Sahu; R. S. Dalvi; Nirupama Chatterjee; S. C. Mukherjee; Kartik Baruah (Fish Physiology and Biochemistry, 2012)

Insulin Receptors and Downstream Substrates Associate with Membrane Microdomains after Treatment with Insulin or Chromium(III) Picolinate - Abeer Al-Qatati; Peter W. Winter; Amber L. Wolf-Ringwall; Pabitra B. Chatterjee; Alan K. Orden; Debbie C. Crans; Deborah A. Roess; B. George Barisas (Cell Biochemistry and Biophysics, 2012)

A Cross-Sectional Exploration of Excessive Daytime Sleepiness, Depression, and Musculoskeletal Pain among Migrant Farmworkers - Joanne C. Sandberg; Joseph G. Grzywacz; Jennifer W. Talton; Sara A. Quandt; Haiying Chen; Arjun B. Chatterjee; Thomas A. Arcury (Journal of Agromedicine, 2012)

Effect of stocking density and journey length on the welfare of rohu (Labeo rohita Hamilton) fry - N. Chatterjee; A. K. Pal; T. Das; R. Dalvi; M. S. Mohammad; K. Sarma; S. C. Mukherjee; K. Baruah (Aquaculture International, 2010)

Quantification and Source Identification of Polycyclic Aromatic Hydrocarbons in Core Sediments from Sundarban Mangrove Wetland, India - C. Domínguez; S. K. Sarkar; A. Bhattacharya; M. Chatterjee; B. D. Bhattacharya; E. Jover; J. Albaigés; J. M. Bayona; Md. A. Alam; K. K. Satpathy (Archives of Environmental Contamination and Toxicology, 2010)

Geological and mineralogical study of eclogite and glaucophane schists in the Naga Hills Ophiolite, Northeast India - Naresh C. Ghose; Om Prakash Agrawal; Nilanjan Chatterjee (Island Arc, 2010)
A variety of low‐ to high‐pressure metamorphic assemblages occur in the metabasic rocks and metachert in the Upper Cretaceous–Eocene ophiolite belt of the central part of the Naga Hills, an area in the northern sector of the Indo–Myanmar Ranges in the Indo–Eurasian collision zone. The ophiolite suite includes peridotite tectonite containing garnet lherzolite xenoliths, layered ultramafic–mafic cumulates, metabasic rocks, basaltic lava, volcaniclastics, plagiogranite, and pelagic sediments emplaced as dismembered and imbricated bodies at thrust contacts between moderately metamorphosed accretionary rocks/basement (Nimi Formation/Naga Metamorphics) and marine sediments (Disang Flysch). It is overlain by coarse clastic Paleogene sediments of ophiolite‐derived rocks (Jopi/Phokphur Formation). The metabasic rocks, including high‐grade barroisite/glaucophane‐bearing epidote eclogite and glaucophane schist, and low‐grade greenschist and prehnite–clinochlore schist, are associated with lava flows and ultramafic cumulates at the western thrust contact. Chemically, the metabasites show a low‐K tholeiitic affinity that favors derivation from a depleted mantle source as in the case of mid‐ocean ridge basalt. Thermobarometry indicates peak P–T conditions of about 20 kb and 525°C. Retrogression related to uplift is marked by replacement of barroisite and omphacite by glaucophane followed by secondary actinolite, albite, and chlorite formation. A metabasic lens with an eclogite core surrounded by successive layers of glaucophane schist and greenschist provides field evidence of retrogression and uplift. Presence of S‐C mylonite in garnet lherzolite and ‘mica fish’ in glaucophane schist indicates ductile deformation in the shear zone along which the ophiolite was emplaced.

Production of xylanase in transgenic tobacco for industrial use in bioenergy and biofuel applications - Aparajita Chatterjee; Narayan C. Das; Sumita Raha; Ruth Babbit; Qingwei Huang; David Zaitlin; Indu B. Maiti (In Vitro Cellular & Developmental Biology - Plant, 2010)

Regulation of tyrosine kinase activity during capacitation in goat sperm - Madhumouli Chatterjee; Pinki Nandi; Swatilekha Ghosh; Parimal C. Sen (Molecular and Cellular Biochemistry, 2010)

Use of a novel anti-proliferative compound coated on a biopolymer to mitigate platelet-derived growth factor-induced proliferation in human aortic smooth muscle cells: comparison with sirolimus - Yong-Dan Tang; Ambarish Pandey; Antonina Kolmakova; Xin-Tong Wang; Subbu S. Venkatraman; Subroto Chatterjee; Freddy Y. C. Boey (Glycoconjugate Journal, 2009)

Post-harvest decline in commerical cane sugar and its relationship with quality parameters in sugarcane under sub-tropical climate - Parul Srivastava; C. Chatterjee; A. K. Shrivastava; S. Solomon; A. K. Srivastava; B. K. Dube (Sugar Tech, 2009)

Flood inundation modeling using MIKE FLOOD and remote sensing data - S. Patro; C. Chatterjee; S. Mohanty; R. Singh; N. S. Raghuwanshi (Journal of the Indian Society of Remote Sensing, 2009)

Mixing ratios of carbonyls and BTEX in ambient air of Kolkata, India and their associated health risk - C. Dutta; D. Som; A. Chatterjee; A. K. Mukherjee; T. K. Jana; S. Sen (Environmental Monitoring and Assessment, 2009)

Organochlorine Pesticide Residues in Sediment Cores of Sunderban Wetland, Northeastern Part of Bay of Bengal, India, and Their Ecotoxicological Significance - S. K. Sarkar; A. Binelli; C. Riva; M. Parolini; M. Chatterjee; A. K. Bhattacharya; B. D. Bhattacharya; K. K. Satpathy (Archives of Environmental Contamination and Toxicology, 2008)

Influence of progressive staling on germination of sugarcane - A. K. Shrivastava; S. Solomon; A. K. Srivastava; S. P. Shukla; A. Sawnani; R. Darash; C. Prajapati; Pushpa Singh; Priyanka Singh; R. K. Rai; R. Jain; Parul Srivastava; et al. (Sugar Tech, 2008)

Structural and Functional Analysis of Rice Catalase-B Gene Promoter: Presence of Dof and CAAT Binding Site - P. Mondal; N. Dey; A. K. Dash; A. Chatterjee; B. B. Sahu; B. Panda; I. B. Maiti; S. C. Sabat (Plant Molecular Biology Reporter, 2007)

Protective role ofPhyllanthus niruri against nimesulide induced hepatic damage - Mary Chatterjee; Parames C. Sil (Indian Journal of Clinical Biochemistry, 2007)

Transgenic Indian mustard (Brassica juncea) expressing tomato glucanase leads to arrested growth of Alternaria brassicae - Kalyan K. Mondal; R. C. Bhattacharya; K. R. Koundal; S. C. Chatterjee (Plant Cell Reports, 2007)

Phytotoxic Effect of Coal Mine Effluent on Growth Behavior, Betabolic Changes, and Metal Accumulation in Rice Plants (Oryza sativa L.) c.v. IR-36 - K. K. Tiwari; S. Dwivedi; U. N. Rai; A. K. Pandey; C. Chatterjee; N. K. Singh; R. D. Tripathi (Bulletin of Environmental Contamination and Toxicology, 2006)

New temperate DNA phage BcP15 acts as a drug resistance vector - D. K. Hens; N. C. Chatterjee; R. Kumar (Archives of Virology, 2006)

Integrating Remote Sensing and GIS Techniques with Groundwater Flow Modeling for Assessment of Waterlogged Areas - C. Chatterjee; Rakesh Kumar; B. Chakravorty; A. K. Lohani; S. Kumar (Water Resources Management, 2005)

Molecular characterization of mulberry genetic resources indigenous to India - K. Vijayan; C. V. Nair; S. N. Chatterjee (Genetic Resources and Crop Evolution, 2005)

Magnesian andesite and dacite lavas from Mt. Shasta, northern California: products of fractional crystallization of H2O-rich mantle melts - Timothy L. Grove; Michael B. Baker; Richard C. Price; Stephen W. Parman; Linda T. Elkins-Tanton; Nilanjan Chatterjee; Othmar Mntener (Contributions to Mineralogy and Petrology, 2005)

Development of a Management Model for a Surface Waterlogged and Drainage Congested Area - Anil K. Lohani; Narayan C. Ghosh; Chandranath Chatterjee (Water Resources Management, 2004)

A Breadth Averaged Numerical Model for Suspended Sediment Transport in Hooghly Estuary, East Coast of India - P. C. Sinha; Pragya Guliani; G. K. Jena; A. D. Rao; S. K. Dube; A. K. Chatterjee; Tad Murty (Natural Hazards, 2004)

A new species of the `Copidognathus tricorneatus' group (Acari: Halacaridae) from India - Tapas Chatterjee; C. Annapurna; Cheon Young Chang (Hydrobiologia, 2004)

Crop Plants as Biological Tools for Assessing and Monitoring Agricultural Lands Inundated with Sewage and Sludge - B. K. Dube; P. Sinha; C. Chatterjee (Bulletin of Environmental Contamination and Toxicology, 2004)

Development of Regional Flood Frequency Relationships Using L-moments for Middle Ganga Plains Subzone 1(f) of India - Rakesh Kumar; C. Chatterjee; Sanjay Kumar; A. K. Lohani; R. D. Singh (Water Resources Management, 2003)

Erosion study of a part of Majuli River-Island using remote sensing data - Pankaj Mani; Rakesh Kumar; C Chatterjee (Journal of the Indian Society of Remote Sensing, 2003)

Persistence and Effectiveness of Iprodione Against Alternaria blight in Mustard - I. Mukherjee; M. Gopal; S. C. Chatterjee (Bulletin of Environmental Contamination and Toxicology, 2003)

Sensitivity Analysis of the GIUH based Clark Model for a Catchment - Rakesh Kumar; C. Chatterjee; A. K. Lohani; Sanjay Kumar; R. D. Singh (Water Resources Management, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Genetic and physiological evidence for the production of N-acyl homoserine lactones by Pseudomonas syringae pv. syringae and other fluorescent plant pathogenic Pseudomonas species - C. Korsi Dumenyo; Asita Mukherjee; Wesley Chun; Arun K. Chatterjee (European Journal of Plant Pathology, 1998)

Mildly alkaline basalts from Pavagadh Hill, India: Deccan flood basalts with an asthenospheric origin - J. D. Greenough; K. R. Hari; A. C. Chatterjee; M. Santosh (Mineralogy and Petrology, 1998)

Suppressive effect of quinalphos on the activity of accessory sex glands and plasma concentrations of gonadotrophins and testosterone in rats - A. Ray; S. Chatterjee; S. Ghosh; S. N. Kabir; A. Pakrashi; C. Deb (Archives of Environmental Contamination and Toxicology, 1991)

Effects of L-ascorbic acid supplementation on dieldrin toxicity in rats - S. K. Bandyopadhyay; R. K. Tiwari; A. Mitra; B. Mukherjee; A. Banerjee; G. C. Chatterjee (Archives of Toxicology, 1982)